Wizyta w Irlandii. Między prawdą historyczną a fikcją literacką = Visit to Ireland. Between historical truth and literary fiction - Gazdecka, Elżbieta; Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Authors of the paper, discuss the proceedings and the significance of John Paul II pilgrimage to Irenland in 1979 in the context of the transcription of papal speeches and press reports. Texts analyzed indicate that the Pilgrim for Peace arrived at Emerald Isle with a mission that could be summarized in two points: 1) faithfullness to catholic tradition of Iris nation; 2) peace in Ulster (and the whole Northern Ireland).
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; pielgrzymka; pilgrimage; Irlandia Północna; Northern Ireland